2020
DOI: 10.1111/ejn.14715
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary movements cause beta oscillations increase and broadband slope decrease in the subthalamic nucleus of parkinsonian patients

Abstract: Periodic features of local field potentials (LFP) are extensively studied to establish the pathophysiological features contributing to Parkinson's disease (PD).Pathological LFP synchronization in the subthalamic nucleus (STN) was assumed to link with motor signs of PD. Commonly, the association between oscillations and clinical signs is studied while the patients are at rest. However, changes in LFPs during movement may reflect particular traits of motor processing in the basal ganglia under PD. Recently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 26 publications
8
36
0
Order By: Relevance
“…This complex pattern of modulation within the beta range may partly explain controversial results about the effect of condition (movement or rest) recorded from heterogeneous PD patients. For instance, previous studies reported higher (Belova et al, 2020;Florin et al, 2013;Kochanski et al, 2019), unchanged (Quinn et al, 2015), and lower (Canessa et al, 2016 (Kühn et al, 2009), and reduced beta activity in the presence of tremor (Hirschmann et al, 2016). These support our finding that higher β 2 power was found in PIGD rather than in TD patients.…”
Section: Stn-lfp Modulation By Phenotype and Movement And Rest Condition: Classical Frequency-band Approachsupporting
confidence: 92%
See 1 more Smart Citation
“…This complex pattern of modulation within the beta range may partly explain controversial results about the effect of condition (movement or rest) recorded from heterogeneous PD patients. For instance, previous studies reported higher (Belova et al, 2020;Florin et al, 2013;Kochanski et al, 2019), unchanged (Quinn et al, 2015), and lower (Canessa et al, 2016 (Kühn et al, 2009), and reduced beta activity in the presence of tremor (Hirschmann et al, 2016). These support our finding that higher β 2 power was found in PIGD rather than in TD patients.…”
Section: Stn-lfp Modulation By Phenotype and Movement And Rest Condition: Classical Frequency-band Approachsupporting
confidence: 92%
“…This complex pattern of modulation within the beta range may partly explain controversial results about the effect of condition (movement or rest) recorded from heterogeneous PD patients. For instance, previous studies reported higher (Belova et al., 2020; Florin et al., 2013; Kochanski et al., 2019), unchanged (Quinn et al., 2015), and lower (Canessa et al., 2016; Cassidy et al., 2002; Kühn et al., 2004) beta‐power after voluntary movement. Moreover, previous works have shown a correlation between pathological beta activity (13–35 Hz) and rigidity/bradykinesia (Kühn et al., 2009), and reduced beta activity in the presence of tremor (Hirschmann et al., 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the PSD decay in humans resulted to be steeper in conditions typically related with increased inhibition, such as NREM sleep [10,25,26] or general anesthesia [17], when compared to wakefulnessas indexed by more negative SE values [25,[27][28][29]. Therefore, the use of SE is gaining popularity also in the study of neurologic conditions [30][31][32][33] Interestingly, more negative SE values (paralleled by reduced E/I ratio) were found over the affected hemisphere in rat models of stroke [34]. Since the SE captures EEG slowing, and is sensitive to alterations in the E/I balance, we expect it to be a reliable measure of the neurophysiological alterations in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] We noted the possibility that the aperiodic (nonoscillatory) component, which is the component of power spectral densities (PSD) in local field potentials (LFP) that does not include the periodic (oscillatory) component, can be a biomarker reflecting behavioral and cognitive states. 23,24 The aperiodic component can be described by a Lorentzian function as 𝐿 = 𝑏 − log(𝑘 + 𝑓 −𝜒 ), where 𝑏 , 𝑘 , and 𝜒 represent the aperiodic offset, the knee parameter, and the aperiodic exponent (see Methods for details). 24 It has been hypothesized that this component reflects physiological information such as the firing rate 25 , excitation-inhibition balance 26,27 , and synaptic currents.…”
Section: Introductionmentioning
confidence: 99%